KRIPTOGRAFI ALGORITMA DES, AES/RIJNDAEL, BLOWFISH UNTUK KEAMANAN CITRA DIGITAL DENGAN MENGGUNAKAN METODE DISCRETE WAVELET TRANSFORMATION (DWT) - Rohmat Nur Ibrahim (Jurnal Computech & Bisnis (e-Journal), 2015)
In the community of information technology users often occur several crimes either consciously or unconsciously, intentionally or unintentionally done. Way to secure data in the form of digital images can use cryptographic technique; cryptography is one of the techniques used to enhance the security aspect of information. Cryptography is the study of science and art to keep a message or data information so that the data is safe. Cryptographic support the needs of the two aspects of information security, namely secrecy (protection of the confidentiality of data information) and authenticity (protection against counterfeiting and alteration of information that is undesirable).Along with the development of computer technology, the world of information technology requires a stronger cryptographic algorithm and secure. Currently, AES / Rijndael (Advanced Encryption Standard) is used as the newest standard cryptographic algorithms. AES / Rijndael replace the DES (Data Encryption Standard), which in 2002 was over its service life. DES is also considered to be no longer able to answer the challenges of the development of communication technology very quickly. AES / Rijndael itself is a cryptographic algorithm using the algorithm AES / Rijndael to encrypt and decrypt the data block along with a 128-bit key length of 128 bits, 192 bits, or 256 bits. Blowfish is an algorithm that uses a block size of 64 bits of data along with the key length of 448 bits. To produce a digital image pixel values randomly needed a method transpormasi Discrete Wavelet (DWT) to generate a random pixel values before the encryption process. So from this comparison produces research in the form of computation time (Computation Time), average shape error (Mean Squared Error), Total changes in pixel values, Level Number of Pixel Change (NPCR), peak signal to noise ratio (PSNR (dB)). Keywords:    Digital imagery, Rijndeal, blowfish, Computation Time, Mean Squared                        Error, Number of Changing Pixel Rate, Peak signal to Noise Ratio